Intrasynovial Injection of Methylprednisolone Acetate in the Treatment of Adhesive Capsulitis of Shoulder: A Retrospective Study - Dam, Bipul Kumar (TAJ: Journal of Teachers Association, 2009)
This study was done in the Out Patient Department of Rajshahi Medical College Hospital. One hundred and sixty two patients of different age group and sex, treated by intrasynovial injection of methylprednisolone acetate were followed up as out patients and were included in the study. Apart from few side effects almost all patients showed good response in respect to pain and joint movement with intrasynovial injection. Out of 21 mild diabetic patients, only 3 patients showed a high level of blood glucose and out of 17 mild hypertensive patients, only 4 patients showed increase in blood pressure. Twelve patients complained of mild face and ankle oedema that gradually subsided after cessation of the treatment. Almost all the patients in this study group were previously treated outside by various types of non-steroidal anti-inflammatory drugs. doi: 10.3329/taj.v15i2.3911 TAJ December 2002; Vol.15(2): 71-73